The safety and efficacy of the 5-HT 1F receptor agonist lasmiditan in the acute treatment of migraine. (2nd September 2017) - Raffaelli, Bianca; Israel, Heike; Neeb, Lars; Reuter, Uwe
ABSTRACT: Introduction : Migraine is among the most disabling disorders worldwide, with a significant therapeutic need. Triptans are drugs of choice in the acute attack treatment, but they are contraindicated in patients with vascular conditions due to their potential vasoconstrictive properties. Further limitations include side effects, inconsistency in therapeutic action and possible non-response. Lasmiditan, a highly selective 5-HT1F receptor agonist, is a novel acute anti-migraine substance devoid of vasoconstriction. Areas covered : This article reviews the clinical efficacy and safety of oral and intravenous lasmiditan as a possible acute migraine treatment. We analyze all currently available results in Phase I to III studies. Expert opinion : Lasmiditan is a promising acute migraine therapy, in particular for patients at cardiovascular risk. Phase II and the first Phase III clinical trials show a significant better headache response in comparison to placebo. The efficacy of lasmiditan proves that vasoconstriction is not essential for acute migraine therapy and thereby points, in addition to a well-established trigeminal contribution, to central neuronal mechanisms in migraine pathophysiology. Lasmiditan penetrates the blood-brain barrier and CNS associated adverse events are common, but mostly in mild to moderate severity. The results of long-term Phase III studies will determine if these adverse events represent a limitation in clinical practice.